IDENTIFIKASI TANAMAN OBAT DI KECAMATAN TALANG KELAPA DAN PEMANFAATAN SERTA SUMBANGSIHNYA PADA MATA PELAJARAN BIOLOGI - Fahmy Armanda (Bioilmi: Jurnal Pendidikan, 2018)
Medicinal plants are plants that can be used for the treatment of diseases with active ingredientscontained in them. Identification of medicinal plants needs to be done because of the variety ofmedicinal plants currently available. This study aims to find out which plants are used as medicine,which parts of the plant are used and how to manage and diseases that can be cured by medicinalplants in Talang Kelapa District. This research is descriptive qualitative with quota samplingtechniques and triangulation techniques as well as data analysis techniques modeled by Miles andHuberman. The results of identification studies in Talang Kelapa District were obtained by 38species from 22 families of medicinal plants. The most used part is leaves, besides the roots, stems,flowers, fruits, rhizomes, sap, tubers and all parts. Some diseases that can be cured by these plantsinclude diabetes, hypertension, cholesterol, fever, diarrhea, itching, canker sores and eliminatemenstrual pain which is processed by mashing then smeared, dripped, dried and pasted, brewedand consumed directly as a vegetable, vegetables or other food mixes. But the management methodthat is in great demand is boiled.